Pengaruh Penerapan Program Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Pegawai Di Kantor Dinas Pemadam Kebakaran Dan Penanggulangan Bencana Kabupaten Gowa - Noviana, Henny Noviana; Mappamiring, Mappamiring; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2021)
This study purpossed to determine the effect of the implementation of occupational safety and health programs on the performance of employees in the Office of Fire and Disaster Management in Gowa Regency. The research method used in this study is a quantitative research method with the type of survey research. The hypothesis put forward is the application of the K3 program to employee performance. Data obtained by 50 respondents, while the sample used is saturated sample. The data analysis technique used is a simple linear regression analysis method with Y = 10.978 + 0.683X with the help of Pearson product moment (r) through the SPSS Version 22.0 program at α = 0.05 level.The results showed that the analysis of occupational safety and health variables were in the unfavorable category at 68.48%, and the analysis of employee performance variables was in the quite good category at 78.64%. And this study shows that the application of the K3 program has an effect on employee performance by 53.5%.